Effects of Calcium on Calmodulin and bFGF/FGF-2 Expression: In Vitro Study on the Sacrouterine Ligament - Rahajeng, Rahajeng; Indriani, Anin; Ninik, Suheni; Nooryanto, M; Agung, I Wayan; Palapa, Heny (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2023)
Objective: To evaluate the effects of calcium on the Sacrouterine Ligament by evaluating the expression of calmodulin and bFGF/FGF-2.Method: A true experimental study was carried out by assessing the cell cultures of sacrouterine ligament from female patients who underwent hysterectomy. The cell cultures were divided into groups that were exposed to calcium at different concentrations of 100 nM, 300 nM, 500 nM, 700 nM, and control group without any exposure. The expression of calmodulin and bFGF/FGF-2 was subsequently analyzed using immunofluorescence and ELISA method.Results: This study showed that exposure to calcium significantly affected calmodulin expression (p-value <0.05). The concentration found to be the most effective to induce calmodulin expression was at 500 nM. Calsium also significantly affected the bFGF/FGF-2 expression (p-value <0.05) with the concentration found to be the most effective to induce bFGF/FGF-2 expression at 500 nM.Conclusion: This study suggested that calcium had a significant positive effect of increasing extracellular matrix expression. A further in vivo study needs to be conducted in order to enhance the evidence of the potential effects to become a preventive agent for pelvic organ prolapse. Calcium is widely available in tropical countries like Indonesia, so this preparation is considered very easy for Indonesian women to apply.Key words: Calcium, calmodulin, bFGF/FGF-2, Extracellular MatrixPengaruh Kalsium pada Ekspresi Calmodulin dan bFGF/FGF-2: Studi In Vitro pada Ligamentum SakrouterinaAbstrakTujuan: Mengevaluasi efek kalsium pada Ligamen Sakrouterina dengan evaluasi ekspresi calmodulin dan bFGF/FGF-2,Metode: Sebuah penelitian true eksperimental dilakukan dengan menilai kultur sel ligamentum sakrouterurina dari pasien wanita yang menjalani histerektomi. Kultur sel dibagi menjadi beberapa kelompok yang diberi paparan kalsium pada konsentrasi yang berbeda yaitu 100 nM, 300 nM, 500 nM, 700 nM, dan kontrol tanpa paparan. Ekspresi calmodulin dan bFGF/FGF-2 selanjutnya dianalisis menggunakan metode ELISA dan imunofluoresensi.Hasil: Penelitian ini menunjukkan bahwa paparan kalsium berpengaruh nyata terhadap ekspresi calmodulin (p-value <0,05). Konsentrasi yang paling efektif untuk menginduksi ekspresi calmodulin adalah pada 500 nM. Kalsium juga berpengaruh nyata terhadap ekspresi bFGF/FGF-2 (p-value <0,05), dengan konsentrasi yang paling efektif untuk menginduksi ekspresi bFGF/FGF-2 adalah pada 500 nM.Kesimpulan: Penelitian ini menunjukkan bahwa kalsium memiliki efek positif yang signifikan terhadap peningkatan ekspresi matriks ekstraseluler. Penelitian in vivo lebih lanjut perlu dilakukan untuk meningkatkan bukti potensi efek sebagai agen pencegahan prolaps organ panggul. Kalsium banyak tersedia di negara tropis seperti Indonesia, sehingga olahan ini dinilai sangat mudah diterapkan untuk wanita Indonesia.Kata kunci: Kalsium, Calmodulin, bFGF/FGF-2, Matriks Ekstraseluler